Estimating the Risk of Deep Brain Stimulation in the Modern Era: 2008 to 2020. Issue 5 (14th August 2021) - Koh, Eun Jeong; Golubovsky, Joshua L; Rammo, Richard; Momin, Arbaz; Walter, Benjamin; Fernandez, Hubert H; Machado, Andre; Nagel, Sean J
Abstract: BACKGROUND: Deep brain stimulation (DBS) was first approved by the United States Food and Drug Administration in 1997. Although the fundamentals of DBS remain the same, hardware, software, and imaging have evolved significantly. OBJECTIVE: To test our hypothesis that the aggregate complication rate in the medical literature in the past 12 years would be lower than what is often cited based on early experience with DBS surgery. METHODS: PubMed, PsycINFO, and EMBASE were queried for studies from 2008 to 2020 that included patients treated with DBS from 2007 to 2019. This yielded 34 articles that evaluated all complications of DBS surgery, totaling 2249 patients. RESULTS: The overall complication rate in this study was 16.7% per patient. There was found to be a systemic complication rate of 0.89%, intracranial complication rate of 2.7%, neurological complication rate of 4.6%, hardware complication rate of 2.2%, and surgical site complication rate of 3.4%. The infection and erosion rate was 3.0%. CONCLUSION: This review suggests that surgical complication rates have decreased since the first decade after DBS was first FDA approved. Understanding how to minimize complications from the inception of a technique should receive more attention.